Synthesis, Sorption Properties of a New Chelating Ion-Exchange Resin Containing β-Resorcylic Acid as the Functional Group and Its Biotechnological Application - Verma, J.K.; G. Verma, Anju (Asian Journal of Chemistry, 2016)
A new chelating ion-exchange resin containing β-resorcylic acid (2,4-dihydroxy benzoic acid) as the functional group, based on macroreticular polystyrene divinylbenzene (8% cross-linked, 18–44 mesh size) has been synthesized. The sorption properties of the chelating ion-exchange resin towards various divalent metal ions, viz., Cu(II), Co(II), Ni(II), Cd(II), Pb(II) and Zn(II) are studied by a static batch equilibration technique, as a function of pH and time of equilibration.